Hubungan Kesulitan Belajar Dengan Prestasi Belajar Siswa Kelas V SD Negeri se-Gugus 21 Kecamatan Ratu Agung - Marince Fitri Yanti; Puspa Djuwita; Lukman Lukman (JURIDIKDAS, 2018)
This study aims to analyze the relationship of learning difficulties with the achievement of 5th grade students of public Elementary School (SD) in the cluster of 21 Sub-Districts of Ratu Agung. The design of this research was quantitative method used a correlational approach. The populations of this research were all of 5th grade students of public Elementary School (SD) in the cluster of 21 Sub-Districts of Ratu Agung and samples of this research took 39 students of 5th grade students of public Elementary School (SD) by using simple random sampling technique. The instrument and colleting the data used in this research was based on Likert Scale and documentation. The technique of analysis data used product moment as correlation formula and test-T. This research showed that rcalculate = 0.572 is bigger than rtable = 0,316, with KP = 32,7%, and tcalculate = 4,231. So it can concluded that there is a significant positive relationship between learning difficulties with the achievement of 5th grade students of public Elementary School (SD) in the cluster of 21 Sub-Districts of Ratu Agung. If the learning difficulties are small then the students’ learning achievement increases.